A Peritumorally Injected Immunomodulating Adjuvant Elicits Robust and Safe Metalloimmunotherapy against Solid Tumors. Issue 41 (4th September 2022) - Zhang, Lingxiao; Zhao, Jing; Hu, Xi; Wang, Chenhan; Jia, Yingbo; Zhu, Chaojie; Xie, Shangzhi; Lee, Jiyoung; Li, Fangyuan; Ling, Daishun
Abstract: Clinical immunotherapy of solid tumors elicits durable responses only in a minority of patients, largely due to the highly immunosuppressive tumor microenvironment (TME). Although rational combinations of vaccine adjuvants with inflammatory cytokines or immune agonists that relieve immunosuppression represent an appealing therapeutic strategy against solid tumors, there are unavoidable nonspecific toxicities due to the pleiotropy of cytokines and undesired activation of off‐target cells. Herein, a Zn 2+ doped layered double hydroxide (Zn‐LDH) based immunomodulating adjuvant, which not only relieves immunosuppression but also elicits robust antitumor immunity, is reported. Peritumorally injected Zn‐LDH sustainably neutralizes acidic TME and releases abundant Zn 2+, promoting a pro‐inflammatory network composed of M1‐tumor‐associated macrophages, cytotoxic T cells, and natural‐killer cells. Moreover, the Zn‐LDH internalized by tumor cells effectively disrupts endo‐/lysosomes to block autophagy and induces mitochondrial damage, and the released Zn 2+ activates the cGas‐STING signaling pathway to induce immunogenic cell death, which further promotes the release of tumor‐associated antigens to induce antigen‐specific cytotoxic T lymphocytes. Unprecedentedly, merely injection of Zn‐LDH adjuvant, without using any cytotoxic inflammatory cytokines or immune agonists, significantly inhibits the growth, recurrence, and metastasis of solid tumors in mice. This study provides a rational bottom‐up design of potent adjuvant for cancer metalloimmunotherapy against solid tumors. Abstract : A simple yet robust immunomodulating adjuvant of Zn 2+ ‐doped layered double hydroxide (Zn‐LDH) is developed to potentiate cancer metalloimmunotherapy without using any cytotoxic inflammatory cytokines or immune agonists. Peritumorally injected Zn‐LDH simultaneously modulates immunosuppressive tumor microenvironment and induces tumor immunogenic cell death, eliciting robust antitumor immunity.